Comparison of Career Adaptability Among Employees of The Bangkok Mass Transit Authority Bus Operations Group - Panidvadtana, Panida; Srihaset, Kamontip; Nuchkong, Vasin (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This study aims to 1. examine the career adaptability of employees at the Bangkok Mass Transit Authority (BMTA), particularly those in the Operations Division of Bus Services, and 2. compare the career adaptability of employees in the same division. The study sample consisted of 366 employees from BMTA's Bus Operations Division 1 and Division 3, including bus drivers and ticket collectors, selected through stratified random sampling. The research tool used was a 24-item career adaptability questionnaire. The data were analyzed using descriptive statistics, including mean, standard deviation, and repeated measures analysis of variance (ANOVA). The results revealed that employees at BMTA's Bus Operations Division 1 and Division 3 demonstrated a high level of overall career adaptability, as well as in each individual component. Specifically, the highest mean score was observed in the dimension of career self-control, followed by career curiosity, career confidence, and career attentiveness, respectively. The repeated measures analysis of variance indicated that the variances in career adaptability components were not equal (Mauchly's W = 0.903, Sig. = 0.000). Furthermore, the Greenhouse-Geisser correction revealed statistically significant differences in the mean scores of the career adaptability components at the 0.05 level (F = 6.773, Sig. = 0.000). Pairwise comparisons showed that employees scored significantly higher in career self-control, career curiosity, and career confidence compared to career attentiveness (p < 0.05).